Cellulose nanocrystal-based poly(butylene adipate-co-terephthalate) nanocomposites covered with antimicrobial silver thin films - Ferreira, Filipe V.; Mariano, Marcos; Pinheiro, Ivanei F.; Cazalini, Elisa M.; Souza, Diego H.S.; Lepesqueur, Laura S.S. [UNESP]; Koga-Ito, Cristiane Y. [UNESP]; Gouveia, Rubia F.; Lona, Liliane M.F. (Wiley, 2019)
In this study, we reported the preparation and prospective application of the nanocomposites of poly(butylene adipate-co-terephthalate) (PBAT) reinforced with cellulose nanocrystals (CNCs). CNCs were isolated from bleached sugarcane bagasse by acid hydrolysis and functionalized with adipic acid. Nanocomposites were prepared with different concentration of CNCs (0.8, 1.5, and 2.3 wt% CNC) by solution-casting method and then were covered with silver thin film by magnetron sputtering. The results showed that the surface modification increased the degree of crystallinity of nanocrystals from 51% to 56%, decreasing their length and diameter. Moreover, AFM-IR spectroscopy revealed that the modified CNCs were covered by adipic acid molecules, improving the dispersion of nanocrystals in PBAT. Well-dispersed modified CNCs acted as heterogeneous nuclei for crystallization of PBAT, and increased the storage modulus of the polymer by more than 200%. These improvements in thermal and mechanical properties of CNC-based PBAT associated with the decrease of 56% in the Escherichia coli biofilm formation on nanocomposites (antibacterial properties) qualify the CNC/PBAT nanocomposites covered with silver thin films to be used as food packaging. POLYM. ENG. SCI., 59:E356–E365, 2019. © 2019 Society of Plastics Engineers.